Kajian Teoritis Pengembangan Bahan Ajar Bahasa Arab - Muhammad Syaifullah; Nailul Izzah (Arabiyatuna: Jurnal Bahasa Arab, 2019)
The need for Arabic language teaching materials is very important in achieving learning objectives. A teacher, student and material is an inseparable unit for success in a learning process. The purpose of what and how the position of teaching materials in learning; includes the role for teachers, students, in classical, individual, and group learning. Principles for the development of Arabic teaching materials; Principles of Socio-Culture, Psychological Principles, and Principles of Language and Education. Then how about the character and steps of developing Arabic teaching materials.Type of library research or library research, which takes data sources from theories in literature. The implications of this study have contributed to the ease of a teacher to develop teaching materials that will be applied to students by paying attention to the principles and characters of the teaching material, namely Arabic.